Creating the college climate, proceedings of the junior college administrative teams institute (2d, Florida State University, tallahassee, July 30-August 3, 1962) - Florida State Univ., Tallahassee; Florida State Univ., Tallahassee; Florida Univ., Gainesville ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1962)
This conference dealt with the various conditions that produce a desirable college atmosphere. These are (1) an able and diverse faculty with an interest in the junior college as a special institution, (2) personnel policies and procedures directed toward the total development of the student, (3) financial and business management providing essential services to both staff and students, (4) an administration capable of keeping the public image of the college in the best possible focus. (hh)
Educational level discussed: Two Year Colleges.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Administration; College Environment; College Faculty; Educational Policy; Financial Policy; School Policy; Student Personnel Services; Two Year Colleges